Adult male circumcision with a circular stapler versus conventional circumcision: A prospective randomized clinical trial - Jin,X.D. (2015)
Male circumcision is the most frequently performed procedure by urologists. Safety and efficacy of the circumcision procedure requires continual improvement. In the present study, we investigated the safety and efficacy of a new male circumcision technique involving the use of a circular stapler. In total, 879 consecutive adult male patients were randomly divided into 2 groups: 441 underwent stapler circumcision, and 438 underwent conventional circumcision. The operative time, pain score, blood loss volume, healing time, treatment costs, and postoperative complications were compared between the two groups. The operative time and blood loss volume were significantly lower in the stapler group than in the conventional group (6.8 ± 3.1 vs 24.2 ± 3.2 min and 1.8 ± 1.8 vs 9.4 ± 1.5 mL, respectively; P<0.01 for both). The intraoperative and postoperative pain scores were significantly lower in the stapler group than in the conventional group (0.8 ± 0.5 vs 2.4 ± 0.8 and 4.0 ±0.9 vs 5.8 ± 1.0, respectively; P<0.01 for both). Additionally, the stapler group had significantly fewer complications than the conventional group (2.7% vs 7.8%, respectively; P<0.01). However, the treatment costs in the stapler group were much higher than those in the conventional group (US$356.60 ± 8.20 vs US$126.50 ± 7.00, respectively; P<0.01). Most patients (388/441, 88.0%) who underwent stapler circumcision required removal of residual staple nails. Overall, the present study has shown that stapler circumcision is a time-efficient and safe male circumcision technique, although it requires further improvement.